(untitled) (American Journal of Technology and Applied Sciences, 2023)
This article is about the methods of using modern technologies of teaching in the primary class and provides feedback on the role and importance of these modern technologies in improving educational efficiency. At the same time, pedagogok also touched on the analysis on the content of the reference of each educator to modern technologies in the process. Again, issues related to the importance of Information Technology in the work of improving and ensuring educational efficiency and the procedure for the application of Information Technology in the elementary grades were also considered.